2008
DOI: 10.2119/2008-00002.steinstraesser
|View full text |Cite
|
Sign up to set email alerts
|

Host Defense Peptides in Wound Healing

Abstract: Host defense peptides are effector molecules of the innate immune system. They show broad antimicrobial action against gram-positive and -negative bacteria, and they likely play a key role in activating and mediating the innate as well as adaptive immune response in infection and inflammation. These features make them of high interest for wound healing research. Nonhealing and infected wounds are a major problem in patient care and health care spending. Increasing infection rates, growing bacterial resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 182 publications
0
114
0
1
Order By: Relevance
“…In a prospective, randomized multicenter trial of 131 patients with posttraumatic and surgical cutaneous lesions a tyrothricin-containing powder demonstrated superior efficacy compared to placebo powder with respect to the radius of lesions as well as to a wound index [23]. There is an increasing interest in AMPs such as tyrothricin because these ‘nature’s antibiotics’ are promising agents for virtually new therapeutic approaches in infectious diseases, especially of the skin and for wound healing [24]. The well-known antimicrobial properties of tyrothricin also apply to the tyrothricin 0.1% gel tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, randomized multicenter trial of 131 patients with posttraumatic and surgical cutaneous lesions a tyrothricin-containing powder demonstrated superior efficacy compared to placebo powder with respect to the radius of lesions as well as to a wound index [23]. There is an increasing interest in AMPs such as tyrothricin because these ‘nature’s antibiotics’ are promising agents for virtually new therapeutic approaches in infectious diseases, especially of the skin and for wound healing [24]. The well-known antimicrobial properties of tyrothricin also apply to the tyrothricin 0.1% gel tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…85 The utilization of peptide based therapies presents an attractive alternative against resistive bacteria. 86 Other alternative treatments have also been explored, including the impact of honey on infection prevention. 87,88 These strategies that look beyond the typical silver and antibiotic based treatments provide potential alternatives to combat antibiotic resistance.…”
Section: Antibacterial Treatment Strategiesmentioning
confidence: 99%
“…At present, data from the literature suggest that AMPs, such as cathelicidin LL-37, HBD-2, HBD-3, psoriasin and RNase 7, are upregulated after skin injury, including burnt skin [5,21,44], whereas cathelicidin expression is low or even absent in the chronic wound stage [6,44]. As LL-37 has a direct effect on wound healing by promoting neovascularization and angiogenesis [5,93], this AMP seems to be the most promising agent for future therapeutic approaches in order to antagonize impaired wound healing.…”
Section: From Bedside To Bench: the Presentmentioning
confidence: 99%
“…However, despite undeniable successes in the preclinical area, only few AMPs have reached the phase of testing in clinical trials so far [45,98,99]. At present, four AMPs were successful in therapeutic clinical trials [5]. Pexiganan, a derivative of magainin, which has been developed for the treatment of infected foot ulcers in patients with diabetes mellitus and which entered phase III trials [45] and has been shown to be equally effective as oral ofloxacin, was finally not approved by the US Food and Drug Administration [98].…”
Section: From Bench To Bedside: the Futurementioning
confidence: 99%
See 1 more Smart Citation